The factors that influence the entrepreneurial decision-making model moderated by Entrepreneurship education - Gustati, Gustati; Santi, Elfitri; Endrawati, Endrawati; Oliyan, Fitra (Politeknik Caltex Riau, 2024)
In implementing Presidential Decree No. 02 of 2022 and Presidential Decree No.08 of 2012, universities as one of the educational institutions in Indonesia include the topic of Entrepreneurship as a compulsory subject in the curriculum. This study aims to provide empirical evidence of the factors that influence the entrepreneurial decision-making model moderated by Entrepreneurship education. This study uses a survey approach, data collection using questionnaires distributed via Google Form. The analysis method used is descriptive analysis, Multiple Regression, and Moderate Regression Analysis. The sample was collected using Purposive Sampling, namely students majoring in Accounting at Politeknik Negeri Padang who have taken Entrepreneurship courses in both D3 and D4 study programs. The results showed that partially the Entrepreneurial Decision was influenced by Profit Expectations, Use of Accounting Information Systems, and Entrepreneurship Education, but was not influenced by the Use of e-commerce. Entrepreneurship Education is able to strengthen entrepreneurial decision making. This research can provide recommendations and evaluations for the government, especially the academics, and entrepreneurs that the importance of Entrepreneurship Education in increasing the growth and development of the economy of Indonesia.